Kemampuan Mengidentifikasi Konjungsi dalam Cerita Rakyat “Terjadinya Lau Kawar” pada Siswa Kelas VIII SMP PAB 5 Tahun Pembelajaran 2022-2023 - Cyndi Oklita; Fita Fatria (Medan Resource Center, 2023)
Conjunctions or connecting words are categories that connect words with words, clauses with clauses, or sentences with sentences or between paragraphs and paragraphs. Conjunctions have many types and functions that are divided, this causes students to not understand the division. Folklore is a cultural heritage of the past that has begun to be forgotten. The purpose of this study is to describe students' ability to identify conjunctions in folklore The occurrence of Lau Kawar in class VIII SMP PAB 5. This research method uses descriptive research with a quantitative approach. The population in this study were 114 grade VIII students, and the sample used was 28 students. The conclusion obtained from this study is the ability of students to identify conjunctions in the Folklore of Lau Kawar by using a description test by class VIII 3 SMP PAB 5 Academic Year 2022-2023 with an average value of 70.71 rounded up to 71 with a standard deviation of 10, 51. The average value is in category B